The Role of PPkn Teachers in Building Student’s Independence Through Character Learning at SMPN 1 Pohjentrek - Alfi Choirotul Ain Hadi; Dewanti Beauty Ari Sutrisno; Niswatul Magfiroh (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This research is motivated by the importance of the role of Civic Education (Civics) teachers in shaping the character of students, especially in building independence as one of the main aspects in student self-development. Independence is an important competency that students must have in order to be able to face the challenges of life positively and responsibly. Therefore, this study aims to examine how the role of Civics Education teachers in building students' independence through character learning at SMPN 1 Pohjentrek.This research uses a qualitative approach with a case study method. The main informants in this research are Civics teachers, and students at SMPN 1 Pohjentrek. Data collection techniques were conducted through in-depth interviews, learning observations, and documentation related to the character learning process. The results showed that Civics teachers have a strategic role in building students' independence through various character learning methods that are consistently applied, such as giving independent assignments, group discussions, and instilling values of responsibility and discipline. In addition, teachers also act as motivators and facilitators who support students to develop self-confidence and initiative in learning. The main finding of this study confirms that character learning guided by Civics teachers can effectively increase the independence of students at SMPN 1 Pohjentrek, so that they are better prepared to face academic and social challenges in the school and community environment